2022
DOI: 10.1128/spectrum.01574-21
|View full text |Cite
|
Sign up to set email alerts
|

Clonal and Horizontal Transmission of bla NDM among Klebsiella pneumoniae in Children’s Intensive Care Units

Abstract: The bla NDM gene is playing an increasingly important role in infections caused by CR-KP, especially in children. However, systematic detection and bioinformatics analysis of NDM-KP in children's hospitals are lacking in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…However, although ceftazidime-avibactam is effective for most KPC- and OXA-48-producing Enterobacteriaceae , it has a narrow antibacterial spectrum which is not available against metallo-beta-lactamase (MBL)-producing Enterobacteriaceae , 31 which is playing an increasingly important role in infections caused by CRE, especially in children. 32 These findings in children require confirmation by randomized controlled trials in the future.…”
Section: Discussionmentioning
confidence: 94%
“…However, although ceftazidime-avibactam is effective for most KPC- and OXA-48-producing Enterobacteriaceae , it has a narrow antibacterial spectrum which is not available against metallo-beta-lactamase (MBL)-producing Enterobacteriaceae , 31 which is playing an increasingly important role in infections caused by CRE, especially in children. 32 These findings in children require confirmation by randomized controlled trials in the future.…”
Section: Discussionmentioning
confidence: 94%
“…It is very concerning that almost identical plasmids could be isolated from epidemiologically unrelated sources. Previous studies also reported the identification of genetically closely related plasmids between those from humans and those from environments, such as hospitals, farm yards, and aquatic environments ( 14 , 26 28 ). Therefore, the use of measures other than antimicrobials, e.g., hand hygiene, patient isolation, minimization of physical contact with animals, and disinfection of the environment, may decrease the spread of bla NDM and bla IMP genes among children.…”
Section: Discussionmentioning
confidence: 98%
“…Carbapenems are among the most effective antimicrobial agents for treating human infections caused by extensively drug-resistant Enterobacterales, mainly E. coli and K. pneumoniae [ 1 ]. However, the intensive use of carbapenems in clinical settings has led to a gradual increase in carbapenem-resistant Enterobacterales (CRE), posing a significant threat to anti-infective treatment, especially among children [ 2 , 3 ]. Notably, carbapenems are not yet approved for use in the livestock industry; however, CRE was prevalent in these sectors [ 4 ].…”
Section: Introductionmentioning
confidence: 99%